Effect of soil amendments on molybdenum availability in mine affected agricultural soils. (15th January 2021) - Wang, Xiaoqing; Brunetti, Gianluca; Tian, Wenjie; Owens, Gary; Qu, Yang; Jin, Chaoxi; Lombi, Enzo
Abstract: Molybdenum (Mo) contamination of agricultural soils around Mo-mining areas is of emerging environmental concern. This study evaluated potential practical techniques for chemical immobilization of three Mo contaminated agricultural soils via application of up to six amendments from four different types of materials including biosolids, biochar supported nanoscale zero-valent iron (BC- n ZVI), drinking water treatment residues (WTR) and ferrous minerals (magnetite and ferrihydrite). The efficacy of the different amendments on soil Mo bioaccessibility and bioavailability was evaluated by monitoring Mo uptake in both monocotyledon (ryegrass) and dicotyledon (alfalfa) plants, soil extractable Mo, and Mo bioavailability as measured by Diffusive Gradient in Thin Films (DGT®). All amendments exhibited no immobilization effect and increased Mo extractability in the severely contaminated soil (264 mg Mo kg −1 ). In contrast, in lightly and moderately contaminated soils (22 and 98 mg Mo kg −1 ), biosolids, WTR and magnetite all reduced soil extractable Mo and decreased Mo uptake in both alfalfa and ryegrass shoots relative to controls (CK). Moreover, DGT showed that during incubation experiments while biosolids amendments increased Mo bioavailability from 115 to 378% compared to the CK treatments, all other amendments decreased Mo bioavailability insignificantly. Graphical abstract: Image 1 Highlights: Across all soils ferrihydrite decreased Mo bioavailability the most consistently. Overall plant type grown significantly affected Mo extractability. Magnetite immobilized Mo more efficiently in moderately contaminated soils. All amendments showed no Mo immobilization in severely contaminated soil. BC- n ZVI exhibited poor Mo chemical immobilization and strong phytotoxicity. Abstract : The research evaluated the chemical immobilization of Mo in contaminated soils used for forage production by applying both 'waste-to-resource' and nanomaterial amendments.